Evaluating a 12-week aerobic exercise intervention in adults with persisting post-concussive symptoms - Leah J. Mercier; Leah J. Mercier; Samantha J. McIntosh; Samantha J. McIntosh; Chloe Boucher; Chloe Boucher; Julie M. Joyce; Julie M. Joyce; Julia Batycky; Julia Batycky; Jean-Michel Galarneau; Joel S. Burma; et al. (Frontiers in Neurology)
BackgroundAlthough guidelines support aerobic exercise in sub-acute mild traumatic brain injury (mTBI), evidence for adults with persisting post-concussive symptoms (PPCS) after mTBI is lacking. The objective was to evaluate the impact of a sub-symptom threshold aerobic exercise intervention on overall symptom burden and quality of life in adults with PPCS.MethodsThis prospective cohort study was nested within the ACTBI Trial (Aerobic Exercise for treatment of Chronic symptoms following mild Traumatic Brain Injury). A total of 50 adults with a diagnosis of mTBI, PPCS and exercise intolerance completed a 12-week sub-symptom threshold aerobic exercise intervention either immediately after enrollment (i-AEP group; n = 27) or following 6-weeks of stretching (d-AEP group; n = 23). Data from all participants (n = 50) were included in the combined AEP (c-AEP) group. The primary outcome was symptom burden on the Rivermead Post Concussion Symptoms Questionnaire (RPQ). Secondary outcomes included measures of quality of life and specific post-concussive symptoms (depressive and anxiety symptoms, functional impact of headache, fatigue, sleep, dizziness and exercise tolerance). Heart rate, blood pressure and heart rate variability were also assessed to understand autonomic function response to intervention.ResultsParticipants were a mean (SD) of 42.6 (10.9) years old (74% female) and 25.1 (14.1) months post-mTBI. Following 12-weeks of intervention participants had a significant improvement in symptom burden on the RPQ (i-AEP: mean change = −9.415, p < 0.001; d-AEP: mean change = −3.478, p = 0.034; c-AEP: mean change = −6.446, p < 0.001). Participants also had significant improvement in quality of life (i-AEP: mean change = 9.879, p < 0.001; d-AEP: mean change = 7.994, p < 0.001, c-AEP: mean change = 8.937, p < 0.001), dizziness (i-AEP: mean change = −11.159, p = 0.001; d-AEP: mean change = −6.516, p = 0.019; c-AEP: −8.837, p < 0.001) and exercise tolerance (i-AEP: mean change = 5.987, p < 0.001; d-AEP: mean change = 3.421, p < 0.001; c-AEP: mean change = 4.703, p < 0.001). Headache (mean change = −5.522, p < 0.001) and depressive symptoms (mean change = −3.032, p = 0.001) improved in the i-AEP group. There was no change in measures of autonomic function.ConclusionA 12-week aerobic exercise intervention improves overall symptom burden, quality of life and specific symptom domains in adults with PPCS. Clinicians should consider prescription of progressive, individualized, sub-symptom threshold aerobic exercise for adults with PPCS even if presenting with exercise intolerance and months-to-years of symptoms.